Heterozygous carriage of a dysfunctional toll-like Receptor 9 Allele Affects CpG Oligonucleotide Responses in B Cells - Knežević, Jelena; Parčina, Marijo; Bekeredjian-Ding, Isabelle (The journal of biological chemistry, 2012)
Toll-like receptors (TLR) are employed by the innate immune system to detect microbial pathogens based on conserved microbial pathogen molecules. For example, TLR9 is a receptor for CpG-containing microbial DNA, and its activation results in the production of cytokines and type I interferons from human B cells and plasmacytoid dendritic cells, respectively. Both are required for mounting an efficient antibacterial or antiviral immune response. These effects are mimicked by synthetic CpG oligodeoxynucleotides (ODN). Although several hyporesponsive TLR9 variants have been reported, their functional relevance in human primary cells has not been addressed. Here we report a novel TLR9 allele, R892W, which is hyporesponsive to CpG ODN and acts as a dominant-negative in a cellular model system. The R892W variant is characterized by increased MyD88 binding and defective co-localization with CpG ODN. Whereas primary plasmacytoid dendritic cells isolated from a heterozygous R892W carrier responded normally to CpG by interferon-α production, carrier B cells showed impaired IL-6 and IL-10 production. This suggests that heterozygous carriage of a hyporesponsive TLR9 allele is not associated with complete loss of TLR9 function but that TLR9 signals elicited in different cell types are regulated differently in human primary cells.